A Systematic Review of Behavioral Change in Motor Neuron Disease and Fronto-Temporal Dementia: Overlap, Differences, and Similarities - Arushi Mishra,; Emily Beswick, (International Journal of Scientific Research in Science and Technology, 2025)
Introduction: Motor neuron disease (MND) is a progressive neurological disorder, previously thought to exclusively affect the motor system. However, we now know that cognitive and behavioral change is also a part of the condition. MND exists on a spectrum with frontotemporal dementia (FTD), with up to 15% of people with MND also meeting diagnostic criteria for FTD. The overlap in symptoms can make diagnosis more difficult but also offer new opportunities for intervention and treatment. Aim: Our aim is to systematically review the academic literature to explore what behavioral symptoms have been identified as occurring in people with MND, FTD and MND-FTD. Method: We conducted a systematic review of academic literature on EMBASE, PubMed and Scopus on the 21st of August 2024. We searched for articles relating to behavioral symptoms in people affected by MND, FTD and MND-FTD using key terms. We included research published in the last ten years. Results: A total of 17 studies were included in the review. The most commonly reported behavioral symptoms were found to be apathy and disinhibition, with 53% and 59% of studies referencing them, respectively. Other commonly reported behavioral symptoms included a loss of sympathy or empathy, hyperorality, and psychosis. Impulsive and compulsive behaviors, along with stereotypies, were also reported, but with less frequency. Conclusion: There was a significant overlap of behavioral symptoms between MND and FTD, with almost all symptoms co-occurring between the two disorders. However, the severity and frequency of these symptoms did differ between MND and FTD, as explored in a few of the studies
Keywords: behavior; motor neuron disease; frontotemporal dementia; amyotrophic lateral sclerosis